EKSPLORASI KEKERASAN SEKSUAL PENYANDANG DISABILITAS DI KOTA AMBON - Sainafat, Adriana; Pelatta, Chendy; Djurumana, Yohana (Jurnal Kebidanan, 2025)
Sexual violence against people with disabilities has been increasing every year. According to a study by the University of Liverpool and WHO in 17 low-income countries, people with disabilities are 3.6 times more likely to experience physical violence and 2.9 times more likely to experience sexual harassment compared to their peers without disabilities. Contributing factors include lack of attention from family, inadequate legal protection, stigma, discrimination, dependence on others, and insufficient education on reproductive health and sexual violence. Therefore, an effective approach is needed. The aim of this study is to explore information from the community of people with disabilities. This is a qualitative study, with informants consisting of school principals, teachers, parents, and students with disabilities. Informants were selected using purposive sampling, and data were collected through interviews, observation, and document review. The results show that the level of sexual violence in Ambon City has increased, and some cases are not reported. People with disabilities are vulnerable to both verbal and non-verbal sexual violence. There is still a lack of special attention from the government, especially for private disabilities, resulting in a shortage of teachers with specific expertise in their fields, which directly impacts parents' knowledge due to the lack of direct education. It can be said that promotive and preventive efforts are still very low. Therefore, a multi-sectoral approach is necessary with the goal of preventing and protecting children with disabilities from sexual violence, so that children with disabilities can avoid stigma and discrimination and have access to health and legal services. The approach model implemented is the one health community approach, which is a multi-sector approach with the single goal of addressing sexual violence against persons with disabilities, serving as self-protection.